PERAN GURU AQIDAH AKHLAK DALAM MENGATASI BULLYING DI MIS AT-TA’AWUN KEDIRI - Waladatuts Tsalitsah Layinatul Aisyiyah; Septiana Purwaningrum; Husnul Khotimah (Institut Agama Islam Negeri Ponorogo, 2023)
Abstrack : The role of the Aqidah Akhlak teacher is needed to internalize Islamic moral values so that students become human beings with noble character. This study aims to find out the forms of bullying, what is the role of the Aqidah Akhlak teacher in overcoming bullying, and the impact of the Aqidah Akhlak teacher's role in overcoming bullying. This study uses a qualitative approach, namely by obtaining data sources from the Aqidah Akhlak teacher and MIS Atta'awun Tugurejo students, Ngasem District, Kediri Regency. Collecting data using interview, observation, and documentation. Data analysis in this study used three stages, namely, the reduction stage, the data presentation stage, the verification stage and conclusions. Checking the validity of the data in this study used source triangulation techniques and technical triangulation. Research Results: 1) The forms of bullying that occurred at MIS Atta'awun Tugurejo, Ngasem District, Kediri Regency were in the category of physical and verbal bullying, such as mocking, scribbling on books, saying dirty words, tearing books, and making fun of friends. 2) The role of the Aqidah Akhlak teacher is to carry out his role as a teacher, namely to provide a good example of speaking and dressing politely. Aqidah Akhlak teachers also provide advice and solutions, then are also able to understand the characteristics of their students, and apply methods that are suitable for their students. 3) The impact of the Aqidah Akhlak teacher's role in overcoming bullying yielded positive results including students being able to self-reflect, not repeating bullying, students feeling guilty and apologizing, and learning in the classroom became more conducive due to reduced bullying.Keyword : role, teacher, bullying, student